2011
DOI: 10.2478/v10181-011-0041-8
|View full text |Cite
|
Sign up to set email alerts
|

The study of canine atopic dermatitis involving the isolation of dogs

Abstract: Twenty-seven pruritic dogs were used in this study. When a hypoallergenic diet was fed to these 27 dogs for six weeks, none of the dogs showed improvement of the pruritus. These dogs had a history and clinical signs of atopic dermatitis (AD) as defined by Prelaud's diagnostic criteria. Subsequently, the 27 dogs were isolated for observation for two weeks in the hospital. In the isolation room in the veterinary clinic, cages and tableware were all stainless steel, and carpet was not used. A hypoallergenic diet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“… Basis for such recommendations: There is still only one uncontrolled study that reported the benefit of house dust mite control with a benzyl benzoate acaricidal spray (Acarosan Spray, Bissell) for reduction of clinical signs of AD in mite-hypersensitive atopic dogs (QOE 2) [ 32 ]. Recently, the isolation of dogs with AD in cages in which house dust mites were controlled was shown to lead to a rapid reduction in pruritus in most dogs with IgE hypersensitivity to environmental allergens (QOE 2) [ 33 ]. B.1.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… Basis for such recommendations: There is still only one uncontrolled study that reported the benefit of house dust mite control with a benzyl benzoate acaricidal spray (Acarosan Spray, Bissell) for reduction of clinical signs of AD in mite-hypersensitive atopic dogs (QOE 2) [ 32 ]. Recently, the isolation of dogs with AD in cages in which house dust mites were controlled was shown to lead to a rapid reduction in pruritus in most dogs with IgE hypersensitivity to environmental allergens (QOE 2) [ 33 ]. B.1.e.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the isolation of dogs with AD in cages in which house dust mites were controlled was shown to lead to a rapid reduction in pruritus in most dogs with IgE hypersensitivity to environmental allergens (QOE 2) [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that ALD constitutes 14 to 25% of CAD, which is similar to that of intrinsic AD in humans (20%) (Tokura 2010, Fujimura 2011, Kabashima et al 2013, Kawano et al 2013, Suto et al 2014. From what we know of the mode of action of CsA, it may be more effective against intrinsic AD, because IL-2 is a Th1 related cytokine and intrinsic AD in humans is Th1-dominant.…”
Section: Discussionmentioning
confidence: 81%
“…An interesting study evaluating the effect of 2-week isolation in 27 dogs with clinical diagnosis of AD showed that 63% of them improved while the rest did not. 42 The improvement was considered most likely due to the allergen avoidance in the hospital environment without furniture and carpets. Among the remaining 37%, 14% (4/27) of these dogs had a negative intradermal allergy testing for all environmental antigens.…”
Section: Intrinsic Ad or Atopic-like Dermatitismentioning
confidence: 99%